Answer:
A
Step-by-step explanation:
Remark
f and d are equal (and acute) because they are corresponding angles.
82 and f are supplementary, so we can find f
Finding f
f + 82 = 180
f = 180 - 82
f = 82
Finding d
d = f
d = 82
Answer:x= 2b/e -c
Step-by-step explanation:
Step-by-step explanation:
Did you mean
Evaluate 3/2 + (-k) + (-2) where k = -5/2
= 3/2 - (-5/2) - 2
= 3/2 + 5/2 - 2
= 8/2 - 2
= 4 - 2
= 2
Answer:
A
Step-by-step explanation:
![\frac{(3x^{2} )^\frac{1}{2} }{3^\frac{1}{2} } =3](https://tex.z-dn.net/?f=%5Cfrac%7B%283x%5E%7B2%7D%20%29%5E%5Cfrac%7B1%7D%7B2%7D%20%7D%7B3%5E%5Cfrac%7B1%7D%7B2%7D%20%7D%20%3D3)
![(3x^2)^\frac{1}{2} = 3^\frac{1}{2} x](https://tex.z-dn.net/?f=%283x%5E2%29%5E%5Cfrac%7B1%7D%7B2%7D%20%3D%203%5E%5Cfrac%7B1%7D%7B2%7D%20x)
Remember that
x^(b-c)
Using that
=3^(1/2x-1/2)=3^((x-1)/2)
![3^\frac{x-1}{2} =3^1](https://tex.z-dn.net/?f=3%5E%5Cfrac%7Bx-1%7D%7B2%7D%20%3D3%5E1)
So we can say:
, because the bases are the same
We can multiply both sides of the equation by 2. We get x-1=2, and x=3. Which is A.
Answer:
-2.5 or - 2 1/2
Step-by-step explanation:
Writing out the expression Mathematically ;
1/3(-15÷1/2)1/4
Using PEMDAS :
Solving the bracket first
(-15 ÷ 1/2) = (-15 * 2/1) = - 30
We have :
1/3(-30)1/4 = - 10 * 1/4 = - 10 / 4 = - 2.5
-2.5 = - 2 1/2